2005
DOI: 10.1209/epl/i2005-10264-2
|View full text |Cite
|
Sign up to set email alerts
|

Generic short-time propagation of sharp-boundaries wave packets

Abstract: A general solution to the "shutter" problem is presented. The propagation of an arbitrary initially bounded wavefunction is investigated, and the general solution for any such function is formulated. It is shown that the exact solution can be written as an expression that depends only on the values of the function (and its derivatives) at the boundaries. In particular, it is shown that at short times ( h / 2 2 mx t << , where x is the distance to the boundaries) the wavefunction propagation depends only on the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 18 publications
(30 reference statements)
2
46
0
Order By: Relevance
“…In quantum matter waves, the Moshinsky shutter or the sudden release of rectangular wave packet is also an example of sharp boundaries. The effects arising in the diffraction patterns due to non-sharp boundaries have been investigated recently [5,50,[70][71][72][73].…”
Section: Diffraction In Timementioning
confidence: 99%
“…In quantum matter waves, the Moshinsky shutter or the sudden release of rectangular wave packet is also an example of sharp boundaries. The effects arising in the diffraction patterns due to non-sharp boundaries have been investigated recently [5,50,[70][71][72][73].…”
Section: Diffraction In Timementioning
confidence: 99%
“…Note that the contribution of the left boundary to the escape probability on the right is O(∆t 3/2 ), (see, e.g., [2], [7], [10]), which is negligible. Adding to (8) the escape probability into the ray x < −1, we obtain the total escape probability…”
Section: Short-time Escape Probabilitymentioning
confidence: 99%
“…Indeed, the short-time escape probability of an initially non-smooth wave function has been discussed several times in the literature [1], [2], [6], [7], [8]. Specifically, it has been shown that in the above mentioned cases the type of discontinuity of the initial wave function determines its escape probability.…”
Section: Introductionmentioning
confidence: 99%
“…However, because the quasi-bound state evolves in time, it gains the integral (41) When the incoming energy is above the minimum eigenenergy (i.e., Ω>Ω min *=U−λ 0 2 /4τ 2 ), there are two times, in which Ω=Ω*(t 1 )=Ω*(t 2 ) (see Figure 9), and due to the temporal symmetry of the perturbation t 1 =−t 2 . Therefore, the particle has two options to be temporally bounded to the quasi-eigenstate: it can either begin at t 1 [33], i.e., (42) the particle cannot survive within the well, and activation is frustrated.…”
Section: Selected Elevations and Forbidden Activationsmentioning
confidence: 99%